SOUNDCSAPE AND THE UNDERSTANDING OF HISTORIC DISTRICTS IN BANDUNG - Widjaja Martokusumo; Heru W Poerbo; Joko Sarwono; Anugrah S. Sudarsono; Ni Putu Amanda Nitidara; Michael Isnaeni Djimantoro; Amanda Arifiana; Feysa A. Poetry (TATALOKA, 2019)
According to UNESCO Convention 1972, cultural heritage consists of tangible and intangible heritage. Soundscape has been considered as a part of the intangible heritage, and it refers to the perceptual quality. In the realm of built environment, perceptual qualities become important concerns, since cultural heritage cannot be described and appreciated using mono-sensorial analysis fundamentally based on vision. As perceptual construct, soundscape has been considered as a new approach in understanding the formation and design of sensitive urban environment. It is argued that perceptual quality, besides visual aesthetics, geographic, psychological and socio-cultural aspects, must be part of the considerations in architecture and urban design. Bandung is well-known for its urban heritage, and as former well-designed colonial town, the historic buildings and areas have morphologically constituted the structure of the inner city. However, the modernization and globalization have led to inevitable transformations, including the destruction of historic places and fabric/district of cultural significance. With the latest urban dynamics, urban environment has also experienced an inescapable process of “sound globalization”, which led to the losing of specific sound-marks in the respective area. This paper is based upon an ongoing research project on strategy for conservation of historic urban areas using soundscape approach. Methodologically, through sound walks, surveys and interviews, several notions relating to urban spatial and formal quality have been collected, assessed and interpreted. The result stands for the understanding of perceptual aspects and quality of urban space in historic urban areas that may contribute to the heritage conservation strategy.